Análise e Avaliação dos Problemas Existentes na Fachada de Arenito do Museu Júlio de Castilhos, Porto Alegre, RS - DI BENEDETTI, VERÔNICA; PHILIPP, RUY PAULO; DE CAMPOS, ROBERTO SACKS (Pesquisas em Geociências, 2007)
<!– .p text-align: justify; –> The Júlio de Castilhos museum of Porto Alegre, formerly used as residence, was built in 1877 by a military engineer Catão Roxo. This building is one of the few examples of urban architecture from the last part of the nineteenth century. Its façade is covered by arenitic and granitic rocks quarried near the city. The covering shows the effects of weathering processes occurred during many years. Some of these were observed during a façade mapping as loss of rocky materials, discoloration, chemical deposition, desintegration and fracturing. Petrographic analyses of the arenite indicate an arcosean composition, rich in quartz, with plagioclase and alkali-feldspar (microcline) and opaque minerals in lesser amounts. The grains have a fine layer of iron oxide (hematite) clad, with a fringe of siliceous cement. The remained pores are filled by clay minerals, mainly illite. The elevated degree of compactation and diagenesis are responsible for the high coherence of the rock, allowing its use as covering rock. The petrographic features (textures and mineralogical composition) indicate that the arenites used on the façade’s museum, comes from the Botucatu Formation. The recognition of the mineral constituents and the knowledge of regional geology allow the façade’s recuperation through the replacing of unrecoverable pieces by new ones.